LITERATURE REVIEW: PERBEDAAN KADAR HEMOGLOBIN SEBELUM DAN SESUDAH PEMBERIAN KOMBINASI TABLET BESI DAN ASAM FOLAT (IFA) PADA REMAJA PUTRI - Sari, Yunita; Triawanti, Triawanti; Muthmainah, Noor (Universitas Lambung Mangkurat, 2023)
Anemia is a nutritional health problem that is still experienced by many women around the world. In this literature review an analysis will be carried out regarding differences in hemoglobin levels before and after administration of a combination of iron and folic acid tablets (IFA) in female adolescents. The review uses the narrative review method. Articles were obtained from keyword searches in the PubMed, Garuda, ProQuest and Google Scholar databases with publications ranging from 2012-2022. A total of 20 articles were analyzed, there were 4,008 female adolescent subjects studied from various countries. A total of 20 articles (100%) showed a difference before and after being given the IFA tablet. Giving IFA tablets every day increased the average hemoglobin level by 0.42-2.3 g/dl, once a week experienced an average increase in hemoglobin levels of 0.2-2.4 g/dl, and twice a week experienced an average increase in hemoglobin levels of 0.53-2.5 g/dl.